2015
DOI: 10.1021/acsnano.5b05903
|View full text |Cite
|
Sign up to set email alerts
|

Mn2+-Doped CdSe/CdS Core/Multishell Colloidal Quantum Wells Enabling Tunable Carrier–Dopant Exchange Interactions

Abstract: In this work, we report the manifestations of carrier-dopant exchange interactions in colloidal Mn(2+)-doped CdSe/CdS core/multishell quantum wells. The carrier-magnetic ion exchange interaction effects are tunable through wave function engineering. In our quantum well heterostructures, manganese was incorporated by growing a Cd0.985Mn0.015S monolayer shell on undoped CdSe nanoplatelets using the colloidal atomic layer deposition technique. Unlike previously synthesized Mn(2+)-doped colloidal nanostructures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
94
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 36 publications
3
94
1
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] These are quasi twodimensional structures grown using relatively inexpensive solution-based synthesis methods, which have a significant cost advantage when compared to molecular beam epitaxy (MBE) and chemical vapor deposition (CVD) growth techniques. In addition, nanoplatelets also offer the following advantages: (a) a tunable emission spectrum, which is narrower than that of colloidal quantum dots (cQDs) 7,9 and (b) an enhanced absorption cross-section. 10 Our previous study of CdSe/CdMnS/CdS core/multi-shell nanoplatelets has shown that the interband emission acquires a net circular polarization of r þ (left circular polarization, LCP) in the presence of an externally applied magnetic field.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8] These are quasi twodimensional structures grown using relatively inexpensive solution-based synthesis methods, which have a significant cost advantage when compared to molecular beam epitaxy (MBE) and chemical vapor deposition (CVD) growth techniques. In addition, nanoplatelets also offer the following advantages: (a) a tunable emission spectrum, which is narrower than that of colloidal quantum dots (cQDs) 7,9 and (b) an enhanced absorption cross-section. 10 Our previous study of CdSe/CdMnS/CdS core/multi-shell nanoplatelets has shown that the interband emission acquires a net circular polarization of r þ (left circular polarization, LCP) in the presence of an externally applied magnetic field.…”
mentioning
confidence: 99%
“…10 Our previous study of CdSe/CdMnS/CdS core/multi-shell nanoplatelets has shown that the interband emission acquires a net circular polarization of r þ (left circular polarization, LCP) in the presence of an externally applied magnetic field. 7 This has been attributed to the exchange interaction between the carrier spins and those of the Mn ions. 11 In contrast, the non-magnetic (CdSe/CdS) core/multi-shell structures exhibit r -(right circular polarization, RCP) net circular polarization when an external magnetic field is applied.…”
mentioning
confidence: 99%
See 3 more Smart Citations